Size does not matter - in the virtual world. Comparing online social networking behaviour with business success of entrepreneurs. (2018) - Gloor, Peter A.; Woerner, Stephanie; Schoder, Detlef; Fischbach, Kai; Colladon, Andrea Fronzetti
We explore what benefits network position in online business social networks like LinkedIn might confer to an aspiring entrepreneur. We compare two network attributes, size and embeddedness, and two actor attributes, location and diversity, between virtual and real-world networks. The promise of social networks like LinkedIn is that network friends enable easier access to critical resources such as legal and financial services, customers, and business partners. Our setting consists of one million public member profiles of the German business networking site XING (a German version of LinkedIn) from which we extracted the network structure of 15, 000 start-up entrepreneurs from 12 large German universities. We find no positive effect of virtual network size and embeddedness, and small positive effects of location and diversity.